Mycobacterium leprae Transcriptome During In Vivo Growth and Ex Vivo Stationary Phases - Ojo, Olabisi; Williams, Diana L.; Adams, Linda B.; Lahiri, Ramanuj (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium leprae, the causative agent of leprosy, is an obligate intracellular pathogen primarily residing within host macrophages and Schwann cells. Whole genome sequencing predicts a highly degraded genome with approximately one third of the coding capacity resulting in the loss of many catabolic pathways. Therefore, it can be assumed that M. leprae obtains many of the necessary metabolites for intracellular survival and growth from the host cells. In this study, global transcriptomic analyses were done on freshly harvested M. leprae growing in athymic mouse footpads for five months (MFP5) and compared to those held in axenic medium for 48 (ML48) and 96 (ML96) hours. Results show that all of the genes and pseudogenes were transcribed under both in vivo and in vitro conditions. 24% and 33% of gene transcript levels were significantly altered in ML48 and ML96 respectively, compared to MFP5. Approximately 45% (39/86) of lipid metabolism genes were significantly downregulated in ML96 compared to MFP5, majority of which are in the β-oxidation pathway. Cholesterol oxidase, acyl-CoA dehydrogenase, and coenzyme F420-dependent oxidoreductase, were significantly upregulated in both ML48 and ML96 compared to MFP5. 30% of cell wall and cell processes functional category genes had altered gene transcription at 96hr compared to MFP5. 40% of 57 genes associated with mycobacterial virulence showed significantly altered transcript levels with 52% significantly downregulated in ML96, including most of the Pro-Glu/Pro-Pro-Glu genes. All 111 hypothetical protein genes with unknown function were expressed. Adenosine triphosphate (ATP) synthesis in M. leprae appears to be significantly downregulated under ex vivo conditions. This is the first study comparing M. leprae global gene expression during in vivo growth and ex vivo stationery phase in axenic medium confirming that during the growth phase in the footpads of experimentally infected mice, M. leprae is metabolically active and its primary source of energy production is probably lipids.